PENGHILANGAN HEMISELULOSA SERAT BAMBU SECARA ENZIMATIK UNTUK PEMBUATAN SERAT BAMBU - Ono Suparno dan Roberto Danieli (Jurnal Teknologi Industri Pertanian, 2017)
*Penulis untuk korespondensiHemicellulose and lignin removal process or degumming of bamboo fibre using cellulase and xylanase was conducted. The objectives of the study were to obtain suitable type of bamboo used in the enzymatic degumming process and to determine the optimum xylanase concentration for the hemicellulose hydrolysis of the selected bamboo. The types of bamboos used in this study were yellow bamboo,ropebamboo,and black bamboo. The study was conducted by enzymatic hydrolyses of the bamboo fibres, and measuring the yield, cellulose content, hemicellulose content, and reducing sugar content. Fibre hydrolysis used the cellulase concentration of 25 U/g and xylanase concentrationsof 50 to 500 U/g. The result showed that yellow bamboo contained cellulose and hemicellulose contents which most susceptible to hydrolysis resulting in reducing sugars, and decreasing cellulose and hemicellule contents of 6.40 % and 12.71%, respectively. The optimum xilanase concentration for the yellow bamboohydolysis was 400 U/g which could hydrolyze hemicellulose by 54.31% in 24 hours.Keywords: bamboo fibre, cellulase, xylanase, hydrolysis, enzymatic process